2023
DOI: 10.1002/adhm.202301728
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Integrated Precise ER‐Targeted and Oxygen‐Compensated Photodynamic Immunostimulant for Immunogenicity‐Boosted Tumor Therapy

Yanrong Qian,
Man Wang,
Yulin Xie
et al.

Abstract: Notwithstanding that immunotherapy has made eminent clinical breakthroughs, activating the immunogenicity and breaking the immunosuppressive tumor microenvironment (ITME) remains tempting yet challenging. Herein, a customized‐designed immunostimulant was engineered for attenuating ITME and eliciting an immune response to address this challenge head‐on. This immunostimulant was equipped with dual silica layers coated upconversion nanoparticles (UCNPs) as nanocarriers modified with N‐p‐Tosylglycine, in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…), as well as to detect, in time and space, As mentioned above, luminescence imaging and drug delivery using LnNPs is another area where preclinical studies have demonstrated their theranostic potential. For example, the UCNPs@polyHPMA-5FU nanosystem is used for luminescence imaging and selective cancer drug delivery [37]. Also relevant is the development of target-specific biomolecules coated on Yb/Er/Ho enriched NaGdF 4 nanoparticles as NIR-II systems for luminescence imaging, MR imaging, X-ray CT imaging, and photodynamic therapy (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), as well as to detect, in time and space, As mentioned above, luminescence imaging and drug delivery using LnNPs is another area where preclinical studies have demonstrated their theranostic potential. For example, the UCNPs@polyHPMA-5FU nanosystem is used for luminescence imaging and selective cancer drug delivery [37]. Also relevant is the development of target-specific biomolecules coated on Yb/Er/Ho enriched NaGdF 4 nanoparticles as NIR-II systems for luminescence imaging, MR imaging, X-ray CT imaging, and photodynamic therapy (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…UCNPs@mSiO 2 -Ce6-GPC3 for PDT in vitro and in vivo. [18,[35][36][37][38][39] Reverse micelle method for hydrophobic ligands.…”
mentioning
confidence: 99%
“…Manipulating the mitochondrial electron transport chain (ETC) enhances tumor immunogenicity, rendering immune-evasive tumors vulnerable to immune surveillance. Dysfunction of complex II (CII) leads to the abnormal transfer of electrons in the ETC, an increase in succinate production and upregulation of the expression of major histocompatibility complex (MHC) and antigen processing and presentation (APP) genes, making GBM more susceptible to cytotoxic T-cell recognition and elimination. Moreover, mitochondrial DNA (mtDNA) possesses CpG motifs, making them vulnerable to mitochondrial reactive oxygen species (mtROS). , Here, we synthesized iridium photosensitizer (IrPS) that electrostatically bind to GBM cell mitochondria by the positive charge after illumination by two-photon light, induce ETC damage, and produce mtROS to oxidize mtDNA. Oxidized mtDNA in GBM can activate the STING pathway, thereby enhancing GBM immune responsiveness and subsequently activating both innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the degradation of the MON led to the release of CQ and CHCA that achieve different goals. First, autophagy inhibitor CQ can inhibit autophagy of tumor cells because it can block the fusion of autophagosomes and lysosomes. , Second, CHCA inhibited lactic acid metabolism by limiting the uptake of lactic acid by tumor cells through the inhibition of MCT1, thereby reducing the intracellular lactic acid concentration. Finally, the reduction of intracellular GSH and the inhibition of lactic acid uptake made tumor cells lose the ability to reduce ROS concentration, while the blocking of autophagy led to the failure of tumor cells to resist ROS damage. Like the “three musketeers”, the three functions of UCNPs@MON@CQ/CHCA@HA broke the tolerance of tumor cells to ROS from different angles, thereby improving the PDT effect and ultimately killing tumor cells.…”
Section: Introductionmentioning
confidence: 99%